2020
DOI: 10.12680/balneo.2020.320
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular electrostimulation as an adjuvant therapy to pulmonary rehabilitation programs in chronic obstructive pulmonary disease

Abstract: Introduction. Chronic obstructive pulmonary disease (COPD) is commonly associated with a vicious circle of sedentary lifestyle - deconditioning - muscular dysfunction. High-frequency neuromuscular electrostimulation has demonstrated beneficial effects among subjects with muscle weakness. This study aimed to evaluate the benefits of merging pulmonary rehabilitation program (PRP) with neuromuscular electrostimulation in patients with very severe COPD. Material and methods. The study included 38 males with clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Likewise, Öncü and Zincir 19 concluded that Acu‐TENS intervention does not affect dyspnea in patients with COPD in the acute exacerbation phase. However, previous studies on patients with COPD and asthma confirmed a reduction in the severity of dyspnea after Acu‐TENS intervention 15–18 . It should be noted that the present study was performed on hospitalized patients who were in the acute phase of the disease, which is similar to the study by Öncü and Zincir 19 .…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Likewise, Öncü and Zincir 19 concluded that Acu‐TENS intervention does not affect dyspnea in patients with COPD in the acute exacerbation phase. However, previous studies on patients with COPD and asthma confirmed a reduction in the severity of dyspnea after Acu‐TENS intervention 15–18 . It should be noted that the present study was performed on hospitalized patients who were in the acute phase of the disease, which is similar to the study by Öncü and Zincir 19 .…”
Section: Discussionsupporting
confidence: 66%
“…However, previous studies on patients with COPD and asthma confirmed a reduction in the severity of dyspnea after Acu‐TENS intervention. 15 , 16 , 17 , 18 It should be noted that the present study was performed on hospitalized patients who were in the acute phase of the disease, which is similar to the study by Öncü and Zincir. 19 Dyspnea is a mental feeling affected by conditions such as weakness, anemia, lack of sleep, fatigue, fear, and anxiety, 28 and physically healthy people may have experienced dyspnea.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations